TINJAUAN YURIDIS MENGENAI TINDAKAN PERUSAHAAN YANG TIDAK MAU MEMBAYAR UANG PESANGON DIHUBUNGKAN DENGAN PASAL 156 UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN JO UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA (STUDI PADA SERIKAT BURUH B - Wahyuni Safitri; Chintya Nora Ningsih (Yuriska: Jurnal Ilmiah Hukum, 2022)
Termination of Employment is the termination of the employment relationship between the company and the employee. Severance pay must be given to workers who have been laid off for normal reasons, such as resignation/retirement but in practice there are companies that are not willing to pay severance pay to workers in the Indonesian Borneo Labor Union. The research uses normative juridical sources from legal materials and interviews. The research focuses on the actions of companies that do not pay severance pay. The results show that the company does not pay severance pay because the worker is considered to have resigned unilaterally but what is considered here is related to the company employing workers/laborers over the age of 60 years who should have retired because they avoid unwanted things such as work accidents, the retirement age is regulated in the Permenaker No. 2 of 1995 Paragraph 1 and Paragraph 2, so that the company is obliged to pay severance pay in Article 156. Type It is recommended that the company pays severance pay in accordance with the provisions of Article 167 Paragraph 5, namely Severance Pay in Article 156 Paragraph 2, severance pay in Article 156 Paragraph 3, Reimbursement of Rights Article 156 Paragraph 4 of Law No. 13 of 2003 concerning Manpower in conjunction with Law No. 11 of 2020 concerning Job Creation and implementing the contents of Decision Number: 83/Pdt.Sus-PHI/2015/PN Smr who already have permanent legal force related to the nominal payment of severance pay due to the termination of the law employment interest because the worker/labourer has retired.